Influence of Alveolar Fluid on Aquaporins and Na+/K+-ATPase and Its Possible Theoretical or Clinical Significance - Zong, Hai-Feng; Guo, Guo; Liu, Jing; Yang, Chuan-Zhong; Bao, Lin-Lin (American Journal of Perinatology, 2021)
Objective Pulmonary edema is the most common pathophysiological change in pulmonary disease. Aquaporins (AQPs) and Na+/K+-ATPase play pivotal roles in alveolar fluid clearance. This study aimed to explore the influence of increased alveolar fluid on the absorption of lung fluid.Study Design Eighty New Zealand rabbits were randomly divided into eight groups (n = 10 in each group), and models of different alveolar fluid contents were established by the infusion of different volumes of normal saline (NS) via the endotracheal tube. Five animals in each group were sacrificed immediately after infusion to determine the wet/dry ratio, while the remaining animals in each group were killed 4 hours later to determine the wet/dry ratio at 4 hours. Additionally, lung specimens were collected from each group, and quantitative real-time PCR (qRT-PCR), western blot, and immunohistochemical (IHC) analyses of AQPs and Na+/K+-ATPase were performed.Results The qRT-PCR analysis and western blot studies showed markedly decreased mRNA and protein levels of AQP1 and Na+/K+-ATPase when the alveolar fluid volume was ≥6 mL/kg, and the mRNA level of AQP5 was significantly reduced when the alveolar fluid volume was ≥4 mL/kg. In addition, IHC analysis showed the same results. At 4 hours, the lung wet/dry ratio was significantly increased when the alveolar fluid volume was ≥6 mL/kg; however, compared with 0 hours after NS infusion, there was still a significant absorption of alveolar fluid for a period of 4 hours.Conclusion The results of this study suggest that increased alveolar fluid may induce the downregulation of the mRNA and protein expression of AQPs and Na+/K+-ATPase, which appear to affect alveolar fluid clearance in rabbit lungs. Early intervention is required to avoid excessive alveolar fluid accumulation.Key Points
Keywords: alveolar fluid; aquaporins; Na+/K+-ATPase; edema resolution